2022
DOI: 10.55198/artibilimfen.1116179
|View full text |Cite
|
Sign up to set email alerts
|

Hidrojen üretimi yoluyla çevre dostu enerji üretiminin incelenmesi

Abstract: Energy production has become one of the most essential elements determining industry, economy, and international relations in the technological development era we are in. Although globalization can help countries surpass their borders, energy strategies are crucial in shaping these relationships. For this purpose, the resources chosen for energy production should be human and ecosystem-friendly, as well as cost-effective and renewable. The hydrogen is suitable energy carrier. In this study, the hydrogen produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Rezvani et al (2015) focused on psychological factors in EV adoption studies and found that psychological barriers such as range, battery life, and charging stations make it difficult for consumers to adapt to electric vehicles. Wang et al (2016) used extended model of TPB to measure consumers’ intention to adopt hybrid electric vehicles (HEV) with attitude, subjective norm, behavioral control effect, and environmental impact (Torun et al, 2019). While environmental influences indirectly affect consumers’ intention to adopt, other factors have been found to have a positive effect on their intention to adopt HEVs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rezvani et al (2015) focused on psychological factors in EV adoption studies and found that psychological barriers such as range, battery life, and charging stations make it difficult for consumers to adapt to electric vehicles. Wang et al (2016) used extended model of TPB to measure consumers’ intention to adopt hybrid electric vehicles (HEV) with attitude, subjective norm, behavioral control effect, and environmental impact (Torun et al, 2019). While environmental influences indirectly affect consumers’ intention to adopt, other factors have been found to have a positive effect on their intention to adopt HEVs.…”
Section: Literature Reviewmentioning
confidence: 99%